Pengaruh Shopping Lifestyle dan Diskon Terhadap Impulsive Buying Produk Aerostreet pada Live Tiktok - Putri Laili Susanti; Sugeng Purwanto (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
The goal of this study is to find out how discounts and a shopping lifestyle affect impulsive Aerostreet product purchases on Live Tiktok. One of the things that can lead someone to make an impulsive purchase of Aerostreet products via Live Tiktok is a person's shopping style and discounts. With 70 respondents, this study focuses on Tiktok social media users. Purposive sampling is used for this study's sampling, and Partial Least Square is used for data analysis. The consequences of this examination show that: 1) Shopping Way of life significantly affects Rash Purchasing of Aerostreet items. 2) Impulsive purchases of Aerostreet products benefit significantly from discounts.